Structure, composition and mechanical properties of multi-layer vacuum-arc nitride coatings - Klymenko, S.; Klymenko, S. An.; Manokhin, А.; Stolbovoy, V.; Beresnev, V.; Šiška, F.; Chlup, Z. (Національний технічний університет "Харківський політехнічний інститут", 2022)
The conditions of application of multilayer vacuum-arc nitride coatings on a substrate made from polycrystalline cubic boron nitride (PCBN) are considered using the samples of (TiAlCrY)N/ZrN, (TiZr/TiSi)N, (TiAlSiY)N/CrN compositions. A schematic diagram of a vacuum-arc installation for applying similar coatings is presented, and the technological conditions of coating formation are considered. The structure and composition of the coatings were studied during diffractometric studies, and the performance of coated tools was examined when turning hardened steel. A large amount of the droplet phase in the (TiAlCrY)N/ZrN coating was established. The lattice parameters of two nitrides with an fcc crystal lattice were determined: ZrN – 4.590 Å, TiAlCrYN – 4.203 Å. CSR (coherent scattering region) of the ZrN phase is 5.4 nm at the microstrain level ε = 4.79·10¯³. High homogeneity and low defects in the thickness of the (TiZr)N/(TiSi)N coating were established – the amount of droplet phase is insignificant. The CSR of the coating is 24.2 nm at the level of microstrain ε = 5.76·10¯³, and the predominant texture orientation is (111). A small amount of the droplet phase was found in the (TiAlCrY)N/CrN coating. Both coating layers are characterized by the formation of phases with a cubic (fcc) crystal lattice, and a strong (111) texture occurs. The crystallographic planes (111) of the phase grains are mainly oriented parallel to the coating interface. The size of the CSR is 14.6 nm. It is shown that multilayer vacuum-arc coatings lead to an increase in the tool life of PCBN cutting tools by reducing the effect of adhesive sticking of the processed material and reducing the intensity of chemical interaction in the cutting zone.

Розглянуто умови нанесення багатошарових вакуумно-дугових нітридних покриттів на підкладку з полікристалічного кубічного нітриду бору (ПКНБ) на прикладі композицій (TiAlCrY)N/ZrN, (TiZr/TiSi)N, (TiAlSiY)N/CrN. Наведено принципова схема вакуумно-дугової установки для нанесення подібних покриттів, розглянуто технологічні умови формування покриттів, запропоновано діаграма режиму роботи випарників та обертання підкладки. Структура і склад покриттів вивчено при дифрактометричних дослідженнях, механічні властивості оцінені з використанням нанотвердоміру «Micron-gamma» з індентором Берковича, працездатність інструментів з покриттям розглянута при точінні загартованої сталі. Встановлено велика кількість краплинної фази у покритті (TiAlCrY)N/ZrN. Визначено параметри гратки двох нітридів з ГЦК кристалічною решіткою: ZrN – 4,590 Å, TiAlCrYN –4,203 Å. ДКР фази ZrN 5,4 нм при рівені мікронапружень ε = 4,79·10¯³. Встановлено висока однорідність і мала дефектність по товщині покриття (TiZr)N/(TiSi)N – кількість краплинної фази незначна. ДКР покриття становить 24,2 нм при рівні мікронапружень ε = 5,76·10¯³, переважна орієнтація текстури (111). Встановлено незначна кількість краплинної фази у покриття (TiAlCrY)N/СrN. У обох шарах покриття характерно утворення фаз с кубічною (ГЦК) кристалічною решіткою, має місце сильна текстура (111). Кристалографічні площини (111) зерна фаз переважно орієнтовані паралельно інтерфейсу покриття. Розмір ДКР становить 14,6 нм. Показано, що багатошарові вакуумно-дугові покриття призводять до збільшення ресурсу роботи різальних інструментів з ПКНБ за рахунок зниження впливу адгезійного налипання оброблюваного матеріалу та зниження інтенсивності хімічної взаємодії в зоні різання та впливі кисню воздуху.
Структура, склад та механічні властивості багатошарових вакуумно-дугових нітридних покриттів
Keywords: vacuum-arc technology; multilayer nitride coatings; composition and mechanical properties of coatings; PVD coatings; PCBN cutting tool; вакуумно-дугова технологія; багатошарові нітридні покриття; механічні властивості покриттів